2020
DOI: 10.21203/rs.3.rs-28398/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lessons Learned from Introducing the Characteristic of an Outstanding Medical Teacher: Its Implication in Role Modeling and Professionalism

Abstract: Background Role models play a crucial role in determining the professional development of medical trainees. The purpose of this qualitative descriptive study is to gain in-depth understanding of the outstanding qualities of one successful role model in Iran. We described his character, personality and merits as a conceptual framework for role modeling in medical education.Methods Qualitative descriptive study. Inductive content analysis was performed, and data were collected by conducting interviews. The study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…This competence is echoed in the literature. A recent survey of mentees who matched into plastic surgery residencies found that items related to a genuine interest in the mentee’s career and personal development and a willingness to set aside time for teaching as the highest-rated attributes (Ahmady et al, 2020; Barker et al, 2016; Braunreiter et al, 2022; Frosch & Goldstein, 2019; Vuk et al, 2021). The mentees from the same study also stressed the importance of one-on-one time with their mentor and listed mentors’ time constraints as a substantial barrier to the mentorship relationship (Barker et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This competence is echoed in the literature. A recent survey of mentees who matched into plastic surgery residencies found that items related to a genuine interest in the mentee’s career and personal development and a willingness to set aside time for teaching as the highest-rated attributes (Ahmady et al, 2020; Barker et al, 2016; Braunreiter et al, 2022; Frosch & Goldstein, 2019; Vuk et al, 2021). The mentees from the same study also stressed the importance of one-on-one time with their mentor and listed mentors’ time constraints as a substantial barrier to the mentorship relationship (Barker et al, 2016).…”
Section: Discussionmentioning
confidence: 99%